Reliability centered maintenance (RCM): quantitative analysis of an induction electric furnace - Cerveira, Diego Santos (2015)
The purpose of this article is to define a maintenance strategy for an electric induction furnace, installed on a special steels Foundry. The research method was the quantitative modeling. The proposed method is based on Reliability-Centered Maintenance (RCM), applied to industrial equipment. Quantitative analysis of reliability, availability and maintainability were used as support the definition of the maintenance strategy of the equipment. For research, historical data were collected from time-to-repair (TTR) and time between failures (TBF) of the equipment under consideration. Supported by ProConf 2000 software, most appropriate distributions have been identified and modeled to TTR (lognormal) and TBF (Weibull). With the results, availability of equipment Av = 98,18% and form factor g = 1 of the Weibull distribution were calculated. It was possible to find a position for the equipment on the bathtub curve, in the maturity phase and define the best maintenance strategy for this case, the predictive maintenance. Finally, the current strategy was discussed and development suggestions were presented to this strategy.